Aspirin and NSAID use and keratinocyte cancers. (1st October 2019) - Pandeya, N.; Olsen, C.M.; Thompson, B.S.; Dusingize, J.C.; Neale, R.E.; Green, A.C.; Whiteman, D.C.; ,
Summary: It is thought that aspirin and other nonsteroidal anti‐inflammatory drugs (NSAIDS) may protect against keratinocyte skin cancers, i.e. squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). However, the evidence for this is scant. The authors, based in Queensland, Australia, studied a group of middle‐aged or elderly Queensland residents obtained from the register of voters (the QSkin study). They compared the incidence of keratinocyte cancers in a three‐year period in individuals who self‐reported taking aspirin or another NSAID regularly, with those who did not. In patients at high risk (such as having a history of previous skin cancer or multiple patches on the skin called actinic lesions) they found that taking aspirin infrequently (less than once a week) was associated with a slightly reduced risk of SCC. Regular use of other NSAIDS (at least once a week) led to a slightly reduced risk of BCCs. In low‐risk patients (no history of skin cancer and fewer than 5 actinic lesions) the authors found no reduced risk from taking aspirin or other NSAIDs. The authors comment that many patients are on low dose aspirin to reduce the risk of heart attacks or strokes, but this may be inadequate to prevent skin cancer. As most patients purchase non‐steroidal drugs over the counter, it was not possible to determine dosage and duration of treatment. They conclude that the protective effect of NSAIDS is slight and only of value in patients at high risk.